Music therapy on non linear assessment of cardiac autonomic function in patients with major depressive disorder - Islam, Shams Ruhani; Ferdousi, Sultana (Journal of Bangladesh Society of Physiologist, 2019)
Background :Non linear measure of heart rate variability (HRV) is an emerging method to detect changes in cardiac autonomic nerve function in major depressive disorder (MDD). Objective: To observe the effect of music therapy on non linear measures of HRV in newly diagnosed MDD patients. Methods: This prospective interventional study was done in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbag, Dhaka in 2018 on 60 newly diagnosed MDD patients aged 20-40 years, both male and female. They were further subdivided into 30 patients with only antidepressant medication (Mirtazapine) and 30 patients received music therapy with Raga kafi (Rabindrasangeet) along with the same medication for 3 months. Age, sex and BMI matched healthy control were also enrolled. HRV non linear parameters were recorded by Power Lab 8/35. For statistical analysis paired sample ‘t’ test and independent sample ‘t’ test were done. Result: SD1, SD2 and SD1/SD2 were found significantly lower in MDD patients compared to healthy control at baseline. After 3 months of music therapy, significant increment of these parameters occurred with trend of improvement in cardiac autonomic nerve function (CANF) in these patients. Conclusion: This study concluded that music therapy can improve CANF by increasing parasympathetic and reducing sympathetic activity in MDD patients. J Bangladesh Soc Physiol. 2019, June; 14(1): 7-13